Play Approach to Improve Learning Outcomes of Squat Style Long Jump in Elementary School Students - Mus, Muslimin; Hudain, Muh. Adnan; Hasyim, Hasyim; Kamaruddin, Ilham; Badaru, Benny (ETDC: Indonesian Journal of Research and Educational Review, 2025)
This study aims to improve the learning outcomes of the basic long jump technique of the squat style in elementary school through the application of a play approach. The type of research used is classroom action research with 29 students as subjects at the fourth-grade level of Islamic Elementary School Unggulan BTN Pemda. The instruments used include an initial test, cycle I, and cycle II, as well as data analysis using SPSS version 21.00. The study was conducted in two cycles, with observations of the difficulties experienced by students and modifications to the learning approach. The results of the initial test indicated that only 27.02% of students achieved learning mastery. After the application of the play approach, in cycle I the learning mastery increased to 54.05%, and in cycle II it reached 81.08% with an average score of 81.03. This increase indicates the effectiveness of the play approach in overcoming difficulties in the basic long jump technique. The application of the play approach has proven effective in improving the learning outcomes of the basic long jump technique of the squat style in fourth-grade students, with learning mastery reaching the standard of 80%. This study provides important implications for the development of physical education learning methodology in elementary schools.